Intelligent techniques for warehousing and mining sensor network data - Cuzzocrea, Alfredo, 1974- (Hershey, Pa : Information Science Reference, 2010)
"This book covers focuses on the relevant research theme of warehousing and mining sensor network data, specifically for the database, data warehousing and data mining research communities"
Includes bibliographical references and index
Keywords: Sensor networks; Data mining; Information retrieval; Computer storage devices